Gender diversity on boards and environmental violations in European firms - Gema C. Fleitas-Castillo; Devora Peña-Martel; Jerónimo Pérez-Alemán; Domingo Javier Santana-Martín (Green Finance)
Knowledge of the impact of board gender diversity on environmental violations in Europe remains limited, as previous literature has focused on socially responsible practices, with less research being directed toward the determinants of corporate actions that harm the environment. This study aimed to address this gap through a multi-theoretical approach and by using different estimation methods. In addition, we used penalties related to environmentally harmful practices, since they represent an appropriate proxy for measuring environmental irresponsibility given that they directly reflect sanctions imposed by regulators and are therefore not subject to manipulation or greenwashing practices. We analyzed a sample of non-financial firms in the STOXX Europe 600 index for 2016–2022. Our findings indicate that board gender diversity leads to a reduction in environmental violations. These results suggest that female directors help mitigate environmental misconduct by improving oversight, enhancing the firm's public image, and facilitating access to essential resources. In addition, board gender diversity improves decision-making and fosters a culture of sustainability by integrating diverse perspectives and approaches. We validated the robustness of our results by using different procedures to address endogeneity issues (OLS, TOBIT, 2SLS, Heckman, and GMM).